Multiple Coordination in Porphyrinoid Hybrid: Changing the Delocalization within the Extended π-System - Pawlicki, Miłosz (Synlett, 2020)
π-Extended and strongly coupled chromophores are constantly explored because of their potential for finding a place in many fields of research focusing on both aspects – the fundamental knowledge and the application studies. The synthetic approach leading to controlled formation of porphyrinoid system with two coordination cores shows an alternative way for controlling the delocalization within the extended π-system. It drastically influences the optic response which after a basic initiator (reversibly) shifts the absorbance to the red region following the significant planarization that increases observed communication between two subunits. Even deeper modification can be done within the system by doping the obtained structure with boron(III) that in addition introduces another switching factor based on Lewis acidity of the introduced metalloid.
Keywords: aromaticity; boron; porphyrinoids; triphyrins; π-delocalization; polycyclic aromatic hydrocarbons (PAHs)